AWE-01 Feasibility and acceptability of novel colonoscopy with computer aided early diagnosis of bowel cancer. (June 2019) - Dolwani, Sunil; Ye, Xujiong; Brain, Katherine; Howe, Robert William; Gubala, Vladimir; Davies, Gemma-Louise; Smits, Stephanie
Abstract : Introduction: Patients with low risk bowel symptoms often triaged to a non-urgent pathway have longer diagnostic intervals and later detection of cancer. Resource and workforce constraints in delivery of secondary care colonoscopy contribute to these delays. This study presents preliminary data to investigate the acceptability and feasibility of a novel type of semi-automated robotic colonoscopy (portable with disposable probes not requiring reprocessing or decontamination) to potentially overcome delays between presentation, referral, diagnosis and treatment decision. Methods: Participants referred by their GP for direct colonoscopy underwent the new procedure (semi-automated robotic colonoscopy) and a parallel (back to back design) standard colonoscopy and were later interviewed via telephone to explore their experience and comparison between the two procedures. Comfort scores and colonoscopy quality indicators and outcomes were compared. An online GP survey exploring feasibility of the new procedure in a primary care setting was also conducted. We also analysed the feasibility and accuracy of developing a machine learning tool to interpret findings at both novel and standard colonoscopy. Results: Participants (6 M, 9 F) perceived the value, usefulness and purpose of the new procedure, with favourable comparisons made to standard colonoscopy, particularly previous experience of pain and recovery. Lack of requirement for sedation was a key benefit of the new procedure. Primary care was endorsed as a location, with proximity and familiarity viewed favourably, particularly in overcoming negative aspects of bowel preparation and recovery (e.g. not wanting to travel far). Those feeling they would not need sedation also viewed primary care positively. Others were indifferent, with feelings that it was such an undesirable procedure that location would not matter. Twenty-nine GPs completed the online survey. Barriers to the new procedure in GP practices included perceived lack of expertise to interpret findings (74% agreement) and not enough space for equipment (59% agreement). Nearly half of participants felt the new procedure had the potential to impact quicker diagnosis (48% agreement), and all participants felt it had the potential to achieve early diagnosis in low risk bowel symptoms not meeting 2 week wait criteria (100% agreement). Conclusions: Target users found the new procedure acceptable and viewed it favourably compared to standard colonoscopy. GPs perceived uses for the new procedure in primary care, particularly for low risk patients, however expertise and space were a concern. These findings are positive as the new procedure has the potential to improve issues with colonoscopy capacity and diagnostic workforce in the NHS, with a larger scale study now needed. We have previously published on the training requirements and learning curve for the novel colonoscopy procedure and will also present data on computer aided analysis and interpretation of findings at colonoscopy.